There’s no such thing as cycle traffic: A critical discourse analysis of public opposition to pro-cycle planning - Robert Egan; Brian Caulfield (Journal of Cycling and Micromobility Research)
Across a variety of low-cycling contexts, there are ambitious targets to reduce private car use and increase cycling to decarbonise everyday mobility practices. A component of many plans to achieve this modal shift is through active travel measures that redistribute rights to space, access or speed in a way that may prioritise cycling over driving. However, public opposition to proposals that might reduce the relative accessibility of driving can limit the possibility and scope of redistributive active travel measures, thereby preventing timely climate action and broader transport system change. In this study, we explored public opposition to a major redistributive active travel scheme proposed in the electoral county of Dún Laoghaire-Rathdown, located within the Dublin Metropolitan Area of Ireland, to examine more broadly how car-based automobility is politically sustained in this unique context. We focused our analysis on 150 public consultation submissions using Faircloughian Critical Discourse Analysis. In this paper, we present several major properties of an oppositional ‘technical discourse of transport planning’, that is normatively car-centric: ‘traffic’ as car-based (im)mobility, roads as ‘traffic’ spaces, ‘traffic’ as an immutable substance, and traffic demand-led planning. We interrogate the historical origins of this discourse in the context of Ireland and consider its effects on planning practices in relation to reproducing car-based automobility. Lastly, we conclude with recommendations that can form part of a counter-discourse that is more compatible with transport decarbonisation targets: wording cycle mobility as ‘cycle traffic’, construing redistributive cycleways as spaces of ‘traffic conversion’ rather than ‘traffic diversion’, and saliently outlining a principle of vision-led planning in redistributive active travel measures, amidst prevailing assumptions that transport planning ought to continue as a primarily ‘demand-led’ practice.